Short Communication: Morpho-agronomic characteristics of twelve accessions of white turmeric (Curcuma zedoaria) germplasm - SITTI FATIMAH SYAHID; RUBI HERYANTO (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Syahid SF, Heryanto R.2017. Short Communication: Morpho-agronomic characteristics of twelve accessions of white turmeric (Curcuma zedoaria) germplasm. Biodiversitas 18: 269-274.White turmeric (Curcuma zedoaria Rosc.) is a potential medicinal plant belong to the family Zingiberaceae. This plant has a good market because of its high demand as raw material for herbal medicine, such as to cure cancer. A germplasm collection of white turmeric collected from different areas of Indonesia is available at Cicurug Research Station of Sukabumi, West Java, Indonesia. Information on characteristics of the accessions, however, are not available yet. This study aimed to determine morphological characters, growth, and yield of 12 accessions of white turmeric. The research was conducted at the Cicurug Research Station from January 2014 to March 2015. Rhizome section of each accession was grown in a 2.5 m x 3.5 m plot at 50 cm x 50 cm plant spacing. The experiment was arranged in a randomized complete block design with three replications. Parameters observed were morphological characters (type of stem, leaf tip, leaf base, leaf shape, stem color, blade color), growth (number of tillers, plant height, number of leaf/stem, leaf length, leaf width, leaf thickness) and yield (rhizome weight, rhizome length, rhizome width, and rhizome thickness) respectively. The results showed that morphological characters, growth, and yields of the 12 accessions observed were varied. All of the characters observed could be evaluated further to determine the important traits. Keywords: Curcuma zedoaria, morphological characters, growth, yield, Zingiberaceae